Defining and Negotiating the Limits of the Immunity of Diplomatic Servants in Eighteenth-Century England - Macfarlane, Karen (Lumen, 2022)
The activities of foreign diplomats in England helped push and create the boundaries of diplomatic privilege in the eighteenth century. One specific issue—the extent to which foreign ministers could shield people from being arrested for debt—led to a sizeable body of case law that defined the limits of the immunity of servants of diplomats. The British government frequently allowed ambassadors to assert privileges even in instances when they were not merited. Diplomatic honour and preservation of good relations were of paramount importance. In addition to the significance to international legal history, the activities of these diplomats and the identity of those whom they sought to protect contribute to the current literature about the complex roles of ambassadors in the eighteenth century. This article addresses the 1708 statute on diplomatic privileges, the vexing question of debt in the eighteenth century, the role of diplomats, the changing case law, and, finally, the means by which matters involving diplomatic privilege avoided the courts altogether.